Honey treatment as a primary dressing for venous leg ulcers: a systematic review. - Flaxman, Polly (2013)
Honey has been used in wound care for thousands of years and following the increase in antibiotic-resistant bacteria it has returned to use in healthcare. Venous leg ulcers are typically very slow healing and are of great cost to the NHS on an annual basis. Therefore, the objective of this review is to assess and evaluate the research on the use of honey as a primary dressing in the treatment of venous leg ulcers. Electronic databases were searched for randomised, controlled trials on the topic. The inclusion criteria included: adult participants with venous leg ulcers recruited from any healthcare setting; honey as the intervention; any comparison to other treatments; wound healing, infection rates and pain as the outcome measures. Included studies were assessed for the risk of bias within the study. No meta-analysis was conducted, a summary of the results has been provided instead. The limitations of this review are that there are few randomised, controlled trials on the subject and the overall quality of the evidence is classed as moderate. This review concluded that it seems honey shows a positive effect in preparing the wound bed of sloughy, infected or macerated venous leg ulcers. However, the results do not show statistically significant results. Therefore, the implications for research are that more large studies on this topic should be conducted.